(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Fairs and festivals are considered as one of the most important motivators for tourism industry. Thus, Rann Mahotsav has become one of the fastest growing segments of tourism. This paper aims to explore and confine the motivational indicators for tourists. The study examines that there are differences in the motivations level between male and female tourists. The main objective of this paper is to examine the impact of motivation level on the basis of gender in Rann Mahotsav.